2004
DOI: 10.1002/hep.20039
|View full text |Cite
|
Sign up to set email alerts
|

The maintenance and generation of membrane polarity in hepatocytes

Abstract: H epatocytes, the major epithelial cells in the liver, are highly polarized. Their plasma membranes are separated by tight junctions into sinusoidalbasolateral and canalicular-apical domains, which contain distinct sets of proteins and lipids. A normal membrane polarity is vital for hepatocytes to perform many diverse functions, such as canalicular bile secretion and simultaneous sinusoidal secretion of large quantities of serum proteins into blood. Hepatocyte polarity is lost in many diseases like cholestasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 62 publications
5
69
0
2
Order By: Relevance
“…7 This difference might be explained by a limited sensitivity of the immunoelectronmicroscopic approach to detect small changes in carrier density in an area as 'large' as the pericanalicular area (defined as a 1 mm zone around the canaliculus) when compared to the amount of carriers in the apical membrane. However, this difference might also confirm observations indicating that Mrp2 is largely retained at the apical membrane in differentiated hepatic cells, while Bsep undergoes dynamic endocytosis and recycles between the canalicular membrane and a subapical region 17,35,36 The potential difference in the dynamics of these two carriers has been linked to differences in linkage to the actinbased cytoskeleton. While Mrp2 interacts via its PDZ domain with ezrin-radixin-moesin (ERM) proteins, 37 which bind directly to actin thereby providing a tight apical retention mechanism, Bsep does not contain a PDZ domain and does probably not interact with ERM proteins.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…7 This difference might be explained by a limited sensitivity of the immunoelectronmicroscopic approach to detect small changes in carrier density in an area as 'large' as the pericanalicular area (defined as a 1 mm zone around the canaliculus) when compared to the amount of carriers in the apical membrane. However, this difference might also confirm observations indicating that Mrp2 is largely retained at the apical membrane in differentiated hepatic cells, while Bsep undergoes dynamic endocytosis and recycles between the canalicular membrane and a subapical region 17,35,36 The potential difference in the dynamics of these two carriers has been linked to differences in linkage to the actinbased cytoskeleton. While Mrp2 interacts via its PDZ domain with ezrin-radixin-moesin (ERM) proteins, 37 which bind directly to actin thereby providing a tight apical retention mechanism, Bsep does not contain a PDZ domain and does probably not interact with ERM proteins.…”
Section: Discussionsupporting
confidence: 75%
“…20 Thus, sorting of Mrp2 and Bsep may be differently regulated. 17 Therefore, we extended our previous immunoelectronmicroscopic investigation by studying density of Bsep in canalicular membranes (without microvilli), canalicular microvilli, and the pericanalicular zone of liver tissue of normal rat livers, rat livers made cholestatic by administration of TLCA and those treated with both, TLCA and TUDCA, identical to those reported recently. 7 …”
mentioning
confidence: 54%
See 2 more Smart Citations
“…Short-term posttranscriptional regulation of Bsep There is considerable evidence from animal models that the canalicular localization of Bsep can be regulated by endo-and exocytotic mechanisms [4,96]. Studies in isolated perfused rat livers showed a stimulation of biliary excretion of bile salts concomitant with a stimulation of vesicular transport processes in hepatocytes [36].…”
Section: Ontogenesis and Regulationmentioning
confidence: 99%